Experimentalism: Aesthetics, Musicology and Conceptual Retroactivity - Borges Pena, Eder Wilker [UNESP] (Assoc Nac Pesquisa & Pos-graduacao & Musica, 2018)
The following work sought to establish a discussion around the definition and acceptance of the concept of experimentalism in music and its various forms of presentation, as well as its opposition to the concept of vanguard. For this, we used writings by composers and theorists on the concept of experimentalism and a review of the aesthetical dictates of various concepts. Next, we present a discussion about the applicability of the concept of experimentalism in aesthetic movements of the first half of the twentieth century and a reflection on the need for conceptual restructuring in musicological studies to certain practices.
Keywords: Experimentalism; Futurism; Dada; Erik Satie; Henry Cowell